Etika Membaca dan Mendengar Al-Qur’ān Perspektif Hadis (Kajian Ma’ān al-Ḥadīṡ) - Khairani, Lili (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
Studying the Qur'ān and ḥadīṡ in human life is very important, so every Muslim has the responsibility to learn how to read, write, understand and appreciate its contents before practicing them in everyday life. The aim of this research is to determine the morals of reading and listening to the Qur'an from the perspective of ḥadīṡ. Using a mauḍu'ī approach, takhrīj al-Ḥadīṡ is the data collection methodology used. In addition, this research data is processed and examined through qualitative presentation that refers to analysis of previously existing data—that is, an organized examination of notes or other documents used as sources of information. Based on research findings, in reading the Qur'an a person must adhere to certain ethical principles that are in line with the teachings of ḥadīṡ Rasūlullāh Saw. In this case, the author succeeded in identifying ethics in interpreting the Al-Qur'ān from the perspective of ḥadīṡ Rasūlullāh Saw. among them: (1) In a pure state. (2) Read slowly. (3) Reading with kusyū'. (4) Starting the reading with ta'āwūż. (5) Read beautifully. As for the ethics of listening to the Qur'ān, information was given by Rasūlullāh through his words that if the Qur'ān is read, a person must listen and not speak, then that person will be rewarded with double goodness. A more explicit statement was made by Wahbah al-Zuḥailī that it is obligatory to hear the Qur'an and listen to it both when it is read in prayer and outside prayer.